PO136 Durable efficacy of cladribine tablets: clarity+extension. (1st December 2017) - Giovannoni, Gavin; Comi, Giancarlo; Cook, Stuart; Rammohan, Kottil; Rieckmann, Peter; Soelberg-Sorensen, Per; Vermersch, Patrick; Hicking, Christine; Adeniji, Abidemi; Dangond, Fernando
Abstract : Background: In CLARITY, cladribine tablets (CT) significantly reduced relapse rates in patients with relapsing multiple sclerosis. CLARITY Extension (EXT) compared the effects of 2 years' additional CT treatment vs no additional treatment. Objective: Assess efficacy of 2 courses of CT or placebo (PBO) in CLARITY and 2 additional courses of CT or PBO in EXT. Methods: Patients receiving PBO in CLARITY were assigned to CT3.5 mg/kg; those treated with CT (3.5 or 5.25 mg/kg) were re-randomised 2:1 to CT3.5 mg/kg or PBO. Annualised relapse rates (ARR) and proportions qualifying relapse free (RF) were compared for CLARITY vs EXT within the same treatment groups: CT3.5 mg/kg in CLARITY and PBO in EXT (n=98); CT3.5 mg/kg in CLARITY and CT3.5 mg/kg in EXT (n=186); CT5.25 mg/kg in CLARITY and CT3.5 mg/kg in EXT (n=186); PBO in CLARITY and CT3.5 mg/kg in EXT (n=244). Results: No significant differences in ARR for CLARITY vs EXT except for PBO in CLARITY and CT3.5 mg/kg in EXT (0.26 vs 0.10, p<0.0001). The proportion RF was similar between CLARITY vs EXT across groups and >70%, except for PBO in CLARITY and CT3.5 mg/kg in EXT (58.0% vs 79.6%, p<0.0001). Conclusions: Clinical benefits were maintained in patients who received CT in CLARITY and PBO in EXT demonstrating durable efficacy.